Alegoria e (anti)bucolismo: da clivagem entre a poesia pastoral greco-latina e as pastorelas alegóricas médio-latinas (Nuntius Antiquus, 2009)
In this article, we attempt to analyse the medieval Latin pastourelles in contrast with the pastoral poetry of the bucolic tradition. We analyse three pastourelles of the Carmina Burana, which in our interpretation have an allegorical meaning: Estivali sub fervore (CB 79), Lucis ordo sidere (CB 157) and Vere dulci mediante (CB 158); we argue that the concept of counter-pastoral as defined by Raymond Williams can be useful to understand the representation of the country in medieval Latin pastourelles, though some reevaluation is necessary. Our conclusion is that the absence of the real social conditions of country life in medieval Latin pastourelles is deeply related to its allegorical content.